The Effects of Development Program in ITERA Dormitory for Student Learning Achievements in First Year Stage Course - Triyana Muliawati; Dewi Suhika (Journal of Science and Applicative Technology, 2019)
The development of student character starts from education process in campus life and residence. The environment is less comfortable and effective in the learning process will affect student achievement. To overcome this, the Institute of Technology of Sumatra (ITERA) provides a new student dormitory which one of the place that can provide an effective learning environment because the coaching programs provided such as peer tutors aim to develop learning achievement in TPB Program. The relationship of coaching program in the dormitory to student achievement on First Year Stage Course (TPB) can be analyze use simple regression method. The data that used in this method are questionnaire, mid test score and final test, especially in Basic Mathematics. The results of the analysis stated that the coaching program at the Dormitory resulted in higher learning achievement than those outside the dormitory.